How much impact will low oil price and carbon trading mechanism have on the value of carbon capture utilization and storage (CCUS) project? Analysis based on real option method - Lin, Boqiang; Tan, Zhizhou (Journal of cleaner production, 2021)
Under climate change policy restrictions, carbon capture utilization and storage (CCUS) is a feasible way for developing countries to meet the energy demand and achieve the goal of carbon dioxide emission reduction at the same time. The common form of carbon dioxide utilization in CCUS is to use carbon dioxide as an oil displacement medium to enhance oil recovery (EOR). However, affected by the global economic downturn and the impact of low oil prices, the future development of CCUS-EOR is full of uncertainty. As a market-oriented policy tool, it is widely recognized that carbon trading mechanism can effectively improve the value of CCUS projects and promote the deployment of CCUS projects. In this context, a deferred option model is proposed to quantitatively evaluate the impact of low oil price shocks and carbon trading mechanism on CCUS-EOR project investment based on real options theory. This model takes uncertain factors such as oil price, carbon price and technological learning rate into account, and provides an analytical framework for relevant investment decisions and policymaking. It is found that the current economic environment is not enough to trigger immediate investment of the CCUS project, but the introduction of a carbon trading mechanism can significantly improve the investment value of the project and reduce the investment failure probability. The sensitivity analysis of key parameters such as carbon price, oil price, and their volatility are carried out. The results show that a higher carbon and oil price is needed to make the optimal investment time of the project move forward. It is suggested that the establishment and improvement of the carbon trading mechanism are useful to promote CCUS-EOR investment. However, to accelerate the development of CCUS-EOR in the short term, it also needs the joint efforts of other powerful policy incentive tools. •A deferred option model is established to evaluate the feasibility of the CCUS-EOR project.•Uncertainties such as oil price and carbon price are considered in this model.•The impact of low oil price shock on the feasibility of the CCUS-EOR project is studied.•The carbon trading market is conducive to enhance the attractiveness of the CCUS-EOR project to investors.•Policy suggestions on CCUS-EOR promotion are discussed.